Historical Background and Implications for Author‘s Rights in the International Bill of Human Rights - Inhye Lee (Journal of Intellectual Property)
The author’s rights or creators’ rights found in Article 27 of the Universal Declaration of Human Rights and Article 15(1)(c) of the International Covenant on Economic, Social and Cultural Rights (ICESCR) cover all scientific, literary, or artistic productions. These articles provide creators with the right to fair remuneration for their labor (material interests), as well as the protection of their moral interests in their productions. This right is notable in international human rights instruments because it includes a specific group of individuals (intellectual workers) in the ICESCR. It is particularly significant because it recognizes the right of authors to protect their moral and material interests as a social and economic right that can require the state to ensure a minimum standard of living. However, it should be recognized that the author’s right of the ICESCR is not the same as the author’s right under intellectual property rights (IPRs). It differs in that it protects only individual creativity, excluding the social functions inherent in IPRs. It is solely the right from a human rights perspective, focusing on the protection of human dignity and creativity. It is also remarkable in terms of ensuring the effectiveness of creators’ protection in the international arena.